PERCENTAGE OF SUCCESSFUL CUTTINGS OF RED STAR BEGONIA PLANTS ON THE USE OF CUTTINGS MATERIAL AND ROOTZONE F - Latifah, Zahrotul; Widiwurjani, Widiwurjani; Sutini, Sutini (International Journal of Multidisciplinary Research and Literature, 2024)
Begonia is an ornamental plant in demand among the public because of its attractive leaf shape. With this, the needs of ornamental plants need to be met. One of them is by doing plant propagation. Plant propagation can be done vegetatively, namely with leaves. The weakness is that the cutting material quickly dries, rots, and dies. It can be overcome by using ZPT(Growth regulator). This research aims to determine the percentage of success of the best cuttings of begonia plants in the combination treatment of cuttings material and several concentrations of Rootone F. The research used a planting model in germination tanks with 25 cuttings. The factors used in the study were cutting material (sliced ​​leaves, whole leaves) and Rootone F concentration (250 ppm, 300 ppm, 350 ppm, 400 ppm) soaked for 30 minutes. Observations were made seven weeks after planting. The research showed that the best combination treatment was whole leaf cuttings and 400 ppm concentration, with the highest percentage of rooted cuttings at 92%, rooted cuttings at 80%, and live cuttings at 80%.